Our house is on fire : scenes of a family and a planet in crisis - Ernman, Malena; Thunberg, Svante, 1969-; Thunberg, Greta, 2003-; Ernman, Beata (New York : Penguin Books, 2020)
"Written by a remarkable family and told through the voice of an iconoclastic mother, Our House Is on Fire is the story of how they fought their problems at home by taking global action. And it is the story of how Greta decided to go on strike from school, igniting a worldwide rebellion"--
Keywords: Ernman, Malena; Thunberg, Greta, -- 2003-; Ernman, Malena -- Family; Mezzo-sopranos -- Sweden -- Biography; Environmentalists -- Sweden -- Biography; Global warming; Autobiographies; Biographies